Methods of Forming Professional Communicative Competence of Future Non-Language Specialists - Oleh LAZARIEV; Yuliia FERNOS; Svitlana KARYCHKOVSKA; Vasyl KARYCHKOVSKYI; Svitlana MASLOVATA; Halyna OSIPCHUK (Communications of International Proceedings, 2020)
Changing the general requirements for the level of training of specialists in higher education establishments requires the introduction of the new methods of work and improvement of traditional ones. The main goal of the study was determined by the need to motivate students while teaching a language, taking into account the principle of individualization of learning, and, most importantly, the need to co-organize work in an interdisciplinary space of requirements for the future non-language specialists to reach the level of professional communicative competence. The concept of "professionally oriented communication" in practice was reduced to the ability to compose a monologue statement and conduct a dialogue within the framework of the topics defined in the curriculum of a foreign language for professional purposes course. Purposeful work on the form of organization of communication, which is always a characteristic feature of professional communication of a specialist, was not singled out as a separate educational goal and was not subject to formation during training speciality language. Among the forms and methods of work, the most significant were those that allow you to create an actual motivation for professional communication and develop the mental and cognitive abilities of students, for example, problem solving tasks. Based on the analysis of the methodological literature, and also, based on the identified shortcomings in the level of proficiency of future specialists in professional communication skills and abilities, we put forward a hypothesis that the targeted training of professional communication skills can be included in the curriculum of a  course of English for specific purposes (ESP).
Keywords: Non-language specialist; English for specific purposes (ESP); professionally oriented communication; communicative competence.